The effect of swimming training on inflammatory cytokines in serum of mice infected depression-type 2 diabetes - Mohadeseh Gilak dalasm; Maghsoud Peeri; Mohammad Ali Azarbaijani (روانشناسی و روانپزشکی شناخت)
Introduction: Clinical and experimental studies have shown that type 2 diabetes is associated with depression-related disorders. Inflammation has been identified as a common mechanism in both type 2 diabetes and depression. Several studies have suggested that swimming exercise might be able to reduce depression-related symptoms Aim: The present research aims to investigate the effect of swimming training on inflammatory cytokines in the serum of rats with depression-type 2 diabetes. Method: The experimental research design is a randomized controlled trial. The statistical population is male C57BL6 mice kept in Pasteur Institute of Iran in 2021. 40 mice were randomly selected and randomly divided into two groups (20 samples in each group). One group became diabetic with a high-fat diet and Streptozotocin. Diabetic samples underwent swimming training for 4 weeks. Then, depression-like behaviors were assessed with Sucrose preference, Novelty-suppressed feeding, Social interaction, and Tail suspension test. We also measured the levels of glucose, insulin and inflammatory cytokines such as IL-1β and TNF-α in the serum of the animals. The data were analyzed by Graphpad Primes. Results: The results indicated that type 2 diabetes significantly increased anhedonia- and depression-like behaviours in mice. Moreover, swimming exercise reduced anhedonia- and depression-like behaviour in type 2 diabetic mice. Swimming exercise also decreased glucose and inflammatory cytokines in the serum of mice with type 2 diabetes. Conclusion: Collectively, this study demonstrates that swimming exercise decreased depression-like behaviour by reducing inflammation in type 2 diabetic mice.Further clinical studies are needed to validate these findings in patients with type 2 diabetes.